2020
DOI: 10.3390/su12229541
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Public Transportation: An Examination of User Behavior to Real-Time GPS Tracking Application

Abstract: Public transportation is an effective method of mobility that promotes cost-saving and is environmentally friendly. Poor public transport ridership in Malaysia is due to the unsatisfactory attitude of public transport users and inaccurate information on departure and arrivals. Sarawak, a state of Malaysia, is especially poor in ridership of public transport. A real-time Global Positioning System (GPS) tracking application (app) was found to be an effective tool to increase the ridership of public transport. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…This study applied the methodology of ranking the priority of each indicator within different dimensions by fuzzy AHP, one of Multi-Criteria Decision Analysis (MDCA), since it allows us to apply the linguistic to evaluate the comparison weight of alternatives to deal with the inherent fuzziness of preference [25,54,55]. The hierarchy framework is developed by considering two levels of evaluation: dimension and indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study applied the methodology of ranking the priority of each indicator within different dimensions by fuzzy AHP, one of Multi-Criteria Decision Analysis (MDCA), since it allows us to apply the linguistic to evaluate the comparison weight of alternatives to deal with the inherent fuzziness of preference [25,54,55]. The hierarchy framework is developed by considering two levels of evaluation: dimension and indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mobility refers to the outcome of APTS implementation to support passenger mobility [22,46,55]. Efficiency is considered the efficiency of a system that reflects a more advanced system, modal share improvement, and user satisfaction [16,30,43], whereas reliability focuses on the continuity and consistency of the system [16,30,43,44].…”
Section: Criteria Category Conditionsmentioning
confidence: 99%
“…An improvement in traffic conditions obviously leads to an improvement in accessibility. Many scholars confirmed that an improvement in traffic conditions can produce space-time convergence and cause the Matthew effect to expand imbalance or cause the trickle-down effect to weaken imbalance between regions [ 37 , 38 ]. Considering such studies are rare in the field of public service facilities, scholars pay more attention to the difference in accessibility to public service facilities under different travel methods [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baghizadeh et al [24] focused on the resilient route to increase the flexibility of the transportation networks to minimize all costs. Chan et al [25] focused on the sustainability of public transportation through an examination of user behavior after real-time GPS tracking application.…”
Section: Introductionmentioning
confidence: 99%
“…Prior researches elucidated two limitations. First, a few number of indicators [9,19,25] had been used, or sustainability frameworks were mostly confined to few dimensions [4,22], such as economic, social, and environmental. Second, equal weighting method [17,18] or AHP method [26,28] has some limitations in measuring sustainable transport.…”
Section: Introductionmentioning
confidence: 99%